Psychotheraphy for rural Malays - does it work? - Md. Zain, Azhar (2003)
Broadly defined, psychotherapy is a process of interaction between two or more individuals in which skills of one is used in the helping relationship for the emotional support and/ or maturation of the other. The history of formal psychotherapy starts in the mid-19th century. At that time Freud experimented with the use of hypnosis in the treatment of neurotic patients. Initially he used hypnosis to suppress symptoms but later used it to release the emotions associated with repressed ideas. In helping patients to recall suppressed events, he found it effective to get the patients to lie on the couch and talk freely about the past while the therapist kept out of sight. This was the origin of free association. He also built an elaborate theory of mental development and functioning to guide his practice. This eventually gave birth to psychoanalysis on which most modern forms of psychotherapy derived. Another well-known definition describes psychotherapy as "an interpersonal process designed to bring ",bout modifications of feelings, cognition, attitudes and behavior which have proved troublesome to the person seeking help from a trained professional." This definition draws attention to three characteristics of psychotherapy: the presence of a therapist-patient relationship; the interpersonal context of the psychotherapies; and, implied by the notion of training and professionalism, the sense that therapies are conducted according to a model that guides the therapist's actions. Psychotherapies are defined in part by their setting and in part by the presence of an explicit model of psychopathology, which in turn generates procedures for relieving distress. Based on this background, some thirteen years ago we embarked on a journey of experimental research to answer the question whether psychotherapy can work on Malay patients from a rural background. Most therapies insist on strict inclusion criteria for their therapies; the major criteria being well educated and psychologically minded patients. This seems to exclude most of the patients we were treating. To do therapy on these patients would mean to defy the criteria and face poor outcome or to create a new form of therapy with our own model and own criteria. We started with neurotic disorders and gradually worked on depression and finally even on psychosis, which has been said to be resistant to psychotherapy, with remarkable success. The work has been recognized and our model of psychopathology and therapy has been included as a form of therapy within the CBT group. Further work is now being geared towards patients with the more severe and chronic forms of anxiety group of disorders.